Effectiveness of carboplatin and paclitaxel as first- and second-line treatment in 61 patients with metastatic melanoma. - Annette Pflugfelder (PLoS ONE, 2011)
BACKGROUND: Patients with metastatic melanoma have a very unfavorable prognosis with few therapeutic options. Based on previous promising experiences within a clinical trial involving carboplatin and paclitaxel a series of advanced metastatic melanoma patients were treated with this combination. METHODS: Data of all patients with cutaneous metastatic melanoma treated with carboplatin and paclitaxel (CP) at our institution between October 2005 and December 2007 were retrospectively evaluated. For all patients a once-every-3-weeks dose-intensified regimen was used. Overall and progression free survival were calculated using the method of Kaplan and Meier. Tumour response was evaluated according to RECIST criteria. RESULTS: 61 patients with cutaneous metastatic melanoma were treated with CP. 20 patients (85% M1c) received CP as first-line treatment, 41 patients (90.2% M1c) had received at least one prior systemic therapy for metastatic disease. Main toxicities were myelosuppression, fatigue and peripheral neuropathy. Partial responses were noted in 4.9% of patients, stable disease in 23% of patients. No complete response was observed. Median progression free survival was 10 weeks. Median overall survival was 31 weeks. Response, progression-free and overall survival were equivalent in first- and second-line patients. 60 patients of 61 died after a median follow up of 7 months. Median overall survival differed for patients with controlled disease (PR+SD) (49 weeks) compared to patients with progressive disease (18 weeks). CONCLUSIONS: Among patients with metastatic melanoma a subgroup achieved disease control under CP therapy which may be associated with a survival benefit. This potential advantage has to be weighed against considerable toxicity. Since response rates and survival were not improved in previously untreated patients compared to pretreated patients, CP should thus not be applied as first-line treatment.